A Constructivist-Ecological Model in Utilizing Collaborative Platforms to Improve Academic Writing Skills: A Conceptual Framework - Sulindra, Eric; Cendra, Anastasia Nelladia; Lestari, Indriana (English Education and Literature Journal (E-Jou), 2026)
In language learning, digital platforms have offered unique opportunities to the learners to expand their skills and competencies beyond their standard level. In academic writing, collaborative platforms, or digital collaborative platforms, have been widely used by writers to achieve their writing goals. However, these platforms have been used in random manners and ways, according to different degrees of the writers’ familiarity to the platforms. There is no structured pattern of how these platforms are effectively used and able to support the writers optimally. Therefore, the paper is conceptualizing a proposed model of how the digital collaborative platforms may function as affordances in supporting the academic writers achieving their goals. The affordances technically function as a bridge between the constructivism approach and the ecological perspective. affordances refer to opportunities for action that the environment provides, which learners perceive and utilize. The learners’ ability to use the affordances determine how they construct the meanings and ideas, especially in their writing. The affordances are available within the environment, creating an ecology for the writers, under the ecological perspective lens. A five-stages model is presented in the paper to explore how a writer is supported by the collaborative platforms in each stage to reach their goals. The stages are initial writing task; interaction with affordances; knowledge construction; feedback and reflection; and finally, development of writing proficiency. The elaboration is done within an ecological perspective and the principles of constructivism. Future research would benefit optimally if focusing more on the empirical aspects of the model and how the effectiveness of digital tools in creating affordances in the five-stage-model intervention